The Influence of Multicultural Education, Cultural Identity, and Political Participation on Minority Rights Awareness in Jakarta - Jemmy, Jemmy; Mokodenseho, Sabil; Yanti, Dawi; Arifannisa, Arifannisa; Mu'min, Halek (Westscience Press, 2024)
This study investigates the dynamics of Multicultural Education, Cultural Identity, and Political Participation in shaping Minority Rights Awareness in Jakarta. A sample of 200 participants provided demographic insights, and a comprehensive structural equation modeling analysis was conducted. The measurement model established reliability and construct validity, with discriminant validity supporting the differences. The structural model revealed that Multicultural Education significantly influenced Minority Rights Awareness, along with substantial impacts of Cultural Identity and Political Participation. This research contributes to the broader discourse on multiculturalism, cultural identity, and political engagement, guiding targeted interventions to increase minority rights awareness in Jakarta.